Current Practice in Ionizing-Radiation Health Examinations at Occupational Health Institutions in Japan: A Nationwide Questionnaire Survey - Hiroko Kitamura; Tatsuo Nagata; Takashi Moritake (Journal of Occupational Health, 2026)
Abstract Objectives To characterize the implementation of ionizing-radiation health examinations at occupational health institutions in Japan and examine how these practices are implemented and interpreted within the current legal framework. We also identified operational factors that may influence their contribution to evaluating radiation-related health effects, fitness for work judgments, and occupational radiation protection. Methods A cross-sectional online questionnaire survey was conducted from January 28 to February 18, 2025, among member institutions listed in the National Federation of Industrial Health Organization directory. Invitations were mailed to 173 institutions, each designating a respondent knowledgeable about examination implementation. Descriptive results were summarized using item-specific denominators and stratified by annual examination volume. Results In total, 90 institutions responded, of which 89 provided ionizing-radiation health examinations. Exposure history was primarily obtained through worker self-report, with limited use of employer documentation or dose records. Lens examinations mainly relied on visual inspection or penlight examination; slit-lamp examination was rare, and retro-illumination imaging was not reported. Skin examinations almost exclusively used unaided visual inspection. Institutions differed in diagnostic classification frameworks and whether personal dose information informed judgment. Conclusions Implementation varied across institutions, particularly in exposure assessment and the use of personal dose information in clinical judgment. This heterogeneity may limit not only the interpretability of examination results but also their contribution to evaluating radiation-related health effects, fitness for work judgments, and occupational radiation protection. These findings highlight the importance of improving the availability and integration of exposure-related information within existing examination processes, particularly in predominantly low-dose occupational environments.